Studies on Growth of Marine Bacteria Using Marine Fish Waste Medium - Sadeeshkumar, R (International Journal of Pharmaceutical & Biological Archive, 2012)
Studies on Growth of Marine Bacteria Using Marine Fish Waste Medium